1994
DOI: 10.1038/ng0894-513
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the gene causing type 1 spinocerebellar ataxia

Abstract: Spinocerebellar ataxia type 1 (SCA1) is a neurodegenerative disorder caused by expansion of a CAG trinucleotide repeat. In this study, we describe the identification and characterization of the gene harbouring this repeat. The SCA1 transcript is 10,660 bases and is transcribed from both the wild type and SCA1 alleles. The CAG repeat, coding for a polyglutamine tract, lies within the coding region. The gene spans 450 kb of genomic DNA and is organized in nine exons. The first seven fall in the 5' untranslated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
181
0
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(185 citation statements)
references
References 31 publications
0
181
0
4
Order By: Relevance
“…SCA1 belongs to the polyglutamine disorders, a group of inherited neurodegenerative diseases caused by expansion of a translated CAG repeat in the coding region of the SCA1 gene (Schols et al, 2004;Orr and Zoghbi, 2007). The characterization of SCA1 (Banfi et al, 1994) allowed ataxin-1 (ATAXIN1) the protein it encodes, to be identified as the molecule responsible for disease pathogenesis and progression. ATAXIN1 is expressed in the CNS throughout life, localized mainly in the nucleus, both in its normal and mutated configuration, with some cytoplasmic localization in cerebellar Purkinje cells .…”
Section: Introductionmentioning
confidence: 99%
“…SCA1 belongs to the polyglutamine disorders, a group of inherited neurodegenerative diseases caused by expansion of a translated CAG repeat in the coding region of the SCA1 gene (Schols et al, 2004;Orr and Zoghbi, 2007). The characterization of SCA1 (Banfi et al, 1994) allowed ataxin-1 (ATAXIN1) the protein it encodes, to be identified as the molecule responsible for disease pathogenesis and progression. ATAXIN1 is expressed in the CNS throughout life, localized mainly in the nucleus, both in its normal and mutated configuration, with some cytoplasmic localization in cerebellar Purkinje cells .…”
Section: Introductionmentioning
confidence: 99%
“…SCA1 is caused by the inheritance of a single copy of ataxin-1 with a polyglutamine-encoding region that ranges from 44 to 82 CAG repeats. 29 Expression of mutant ataxin-1 leads to ataxia that progressively worsens over time, loss of Purkinje cells and brainstem neurons and cerebellar atrophy. Mutant ataxin-1, like the amino terminus of mutant huntingtin, translocates to the nucleus where it forms inclusion bodies.…”
Section: Dominantly Inherited Neurologic Diseases Induced By Nucleotimentioning
confidence: 99%
“…In contrast, the length of expanded CAG repeat in the SCA1 disease chromosomes ranges from 39 up to 81 repeats. The length of expansion is inversely correlated with age-of-onset of disease, suggesting a direct role of CAG repeat/polyglutamine length in the pathogenesis of SCA1 Orr et al 1993;Banfi et al 1994).…”
Section: Introductionmentioning
confidence: 98%
“…Spinocerebellar ataxia type 1 (SCA1) (OMIM: #164400) is caused by an expansion of trinucleotide (CAG) repeat that encodes polyglutamine tract in the ataxin-1 (ATXN1) gene (OMIM: *601556) lying in the short arm of human chromosome 6 (6p23) Orr et al 1993;Banfi et al 1994). In normal chromosomes, this CAG repeat shows repeat-length polymorphism ranging in size between 19 and 39 repeats.…”
Section: Introductionmentioning
confidence: 99%